Crack resistance of carbonized layer of multilayer polyurethane with nanofillers. Combination of casting, solution, carbonization by ion implantation technologies - R. I. Izyumov; A. L. Svistkov; V. S. Chudinov; I. V. Osorgina; A. G. Pelevin (Fracture and Structural Integrity)
The paper describes the results of an experimental study of a polyurethane material treated by ion implantation technology. The problems of crack growth in the near-surface layer carbonized by ion treatment were investigated using digital optical microscopy. The methods of atomic force microscopy allowed studying the possibility of carbonized layers delamination from the substrate. As a result, the technology for the production of a multilayer polyurethane material with nanofillers (nanotubes, nanodiamonds, fullerenes, graphenes) and its optimal modification by ion implantation treatment was developed, which makes it possible to improve the biocompatibility of polyurethane implants with human tissues